Controlling The Cost Through Target Costing - Alagappan, Latha (2004)
Target costing has recently received more attention due to the increased competition and customer's ever increasing demand for a wide variety of products. It is adopted mainly in the manufacture of electronic products and Automobiles. The researchers in target costing have concentrated most of all in the innovation of a new product. The research is focused in the achievement of target cost for an existing product. The research involves a case analysis of two companies explaining how far they could achieve the target cost.